2006
DOI: 10.1193/1.2206791
|View full text |Cite
|
Sign up to set email alerts
|

Natural Warning Signs of Tsunamis: Human Sensory Experience and Response to the 2004 Great Sumatra Earthquake and Tsunami in Thailand

Abstract: f…Natural warning signs of tsunamis include ground shaking from earthquakes and unusual sea-level fluctuations, wave forms, and sounds. These signs can alert people to impending tsunamis, but no research has explored the recognizability of these signs or the social-cognitive factors that affect human behavioral response to them. Of 663 interviewees, 24% felt ground shaking during the earthquake; 69% saw something unusual about the ocean before the first wave reached land, mostly a receded shoreline; and 55% he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…Similarly, this applies for the second assumption made: the assumed reaction time of two minutes is rather short and implies that people understand an issued warning, that they know how to respond to it and that they know how to reach a safe place. Gregg et al (2006) presented in their study that, although 69% of the people had observed the receding shoreline prior to the tsunami, most of them did not evacuate. 79% of the surveyed population had to evacuate multiple times as their inital "safe" place proved unsafe (Gregg et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, this applies for the second assumption made: the assumed reaction time of two minutes is rather short and implies that people understand an issued warning, that they know how to respond to it and that they know how to reach a safe place. Gregg et al (2006) presented in their study that, although 69% of the people had observed the receding shoreline prior to the tsunami, most of them did not evacuate. 79% of the surveyed population had to evacuate multiple times as their inital "safe" place proved unsafe (Gregg et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Gregg et al (2006) presented in their study that, although 69% of the people had observed the receding shoreline prior to the tsunami, most of them did not evacuate. 79% of the surveyed population had to evacuate multiple times as their inital "safe" place proved unsafe (Gregg et al, 2006). These data demonstrate that socialization and education of the population including awareness raising for the risk and familiarization with natural and institutional warning signs and messages, evacuation routes and safe places should therefore be core elements of risk reduction strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become clear that there are extant indigenous traditions that have elicited appropriate responses from communities confronted by disaster in ways that may be more effective than nonindigenous, science-based warning systems (McAdoo et al 2006;McAdoo, Moore, and Baumwoll 2009). Conversely, it is also apparent that many peripheral (distant from urban) communities in developing countries today lack such traditions and consequently have a need to interpret precursors of disaster to enable appropriate responses (Gregg et al 2006;Gaillard et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Earthquake ground shaking is often not interpreted by people as a tsunami warning (Gregg et al, 2006), therefore not all people evacuate the hazard zone. Compliance rate is little-studied for local-source tsunami, but may be influenced by proximity to the shoreline, property ownership, age and preparation of household plans (Charnkol and Tanaboriboon, 2006;Murakami and Kashiwabara, 2011).…”
Section: Evacuation Departure Time (Id T + Ep T )mentioning
confidence: 99%